Asset liquidity, capital structure, and secured debt - Morellec, E (Journal of Financial Economics, 2001)
This paper investigates the impact of asset liquidity on the valuation of corporate securities and the firm's financing decisions. I show that asset liquidity increases debt capacity only when bond covenants restrict the disposition of assets. By contrast, I demonstrate that, with unsecured debt, greater liquidity increases credit spreads on corporate debt and reduces optimal leverage. The model also determines the extent to which pledging assets increases firm value and relates the optimal size of the pledge to firm and industry characteristics. Finally, I show that asset liquidity and security provisions may help explain leverage ratios and credit spreads observed in practice.